Evolutionary seroepidemiology of viral hepatitis and the gap in hepatitis C care cascades among uraemic patients receiving haemodialysis in Taiwan—the Formosa‐Like Group. Issue 5 (13th February 2021) - Wei, Yu‐Ju; Hsu, Po‐Yao; Lee, Jia‐Jung; Niu, Sheng‐Wen; Huang, Jiun‐Chi; Hsu, Cheng‐Ting; Jang, Tyng‐Yuan; Yeh, Ming‐Lun; Huang, Ching‐I; Liang, Po‐Cheng; Lin, Yi‐Hung; Hsieh, Ming‐Yen; et al.
Abstract: Uraemic patients undergoing haemodialysis are at high risk of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. We aimed to evaluate the evolutionary seroprevalence of viral hepatitis and the gap in HCV care cascades in this special population by a large‐scale surveillance study in Taiwan. Uraemic patients on maintenance haemodialysis from 22 sites (FORMOSA‐LIKE group) in 2012 (n = 1, 680) and 2019 (n = 2, 326) were recruited for this study. The distributions and sequential changes of viral hepatitis markers were analysed. The prevalence of anti‐HCV antibody and hepatitis B surface antigen (HBsAg) seropositivity was 13.6% (316/2326) and 11.5% (267/2326), respectively, in 2019 compared with 17.3% (290/1680, P = .002) and 13.6% (229/1680, P = .046), respectively, in 2012. The HCV‐viremic rate among anti‐HCV‐seropositive patients was significantly lower in 2019 than in 2012 (56.3% [178/316] vs. 73.8% [214/290], P < .001). The HCV treatment rate increased from 2.3% (5/217) in 2012 to 21.7% (49/226) in 2019 (P < .001). In the sequential analysis of the 490 patients who participated in both screens, 17 of the 55 HCV‐viremic patients became HCV RNA seronegative, including 13 by antivirals and four spontaneously. By contrast, one anti‐HCV‐seropositive but nonviremic patient became viremic, and six anti‐HCV‐seronegative patients became anti‐HCV‐seropositive in 2019. The annual incidence of new HCV was 0.2%/year. Seven HBsAg‐seropositive patients experienced HBsAg loss (1.25%/year). Two patients had new anti‐HBc seropositivity (new HBV exposure: 0.57%/year). The seroprevalence of viral hepatitis decreased in an 8‐year follow‐up but remained prevalent, and the treatment of HCV infection was underutilized in uraemic patients. Additional efforts are needed to enhance the HCV treatment uptake of uraemic patients. Clinical Trial IDs: NCT03803410, NCT01766895.